1998
DOI: 10.1093/jn/128.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Free Red Wine Enhances Plasma Antioxidant Capacity in Humans

Abstract: Moderate wine consumption is reputed to exert a protective effect against coronary heart disease (CHD). The nature of the protective compounds is unclear and the mechanisms are incompletely understood. We studied whether the nonalcoholic component of wine increases plasma antioxidant capacity measured as total radical-trapping antioxidant parameter (TRAP), and whether such an effect is associated with the presence of phenolic compounds in plasma. The TRAP and plasma levels of phenolic compounds were measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
223
2
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(240 citation statements)
references
References 39 publications
10
223
2
5
Order By: Relevance
“…Relatively high peak plasma levels of quercetin, the predominant¯avonoid in red wine, occur within 1 ± 4 h after consumption of¯avonol rich foods (Hollman et al, 1997). This might explain the increased plasma antioxidant capacity directly following ingestion of red wine as reported by many Maxwell et al, 1994;Whitehead et al, 1995), and also agrees with the ®nding that alcohol-free red wine increases plasma antioxidant capacity (measured as total radical-trapping antioxidant parameter, TRAP) 50 min after ingestion and returns to baseline again 70 min later (Sera®ni et al, 1998). The TEAC of the red wine we used is in accordance with published antioxidant values of red wine (Verhagen et al, 1996;Campos & Eduardo, 1996).…”
Section: Discussionsupporting
confidence: 77%
“…Relatively high peak plasma levels of quercetin, the predominant¯avonoid in red wine, occur within 1 ± 4 h after consumption of¯avonol rich foods (Hollman et al, 1997). This might explain the increased plasma antioxidant capacity directly following ingestion of red wine as reported by many Maxwell et al, 1994;Whitehead et al, 1995), and also agrees with the ®nding that alcohol-free red wine increases plasma antioxidant capacity (measured as total radical-trapping antioxidant parameter, TRAP) 50 min after ingestion and returns to baseline again 70 min later (Sera®ni et al, 1998). The TEAC of the red wine we used is in accordance with published antioxidant values of red wine (Verhagen et al, 1996;Campos & Eduardo, 1996).…”
Section: Discussionsupporting
confidence: 77%
“…Similar increases in the ability of plasma to resist oxidative challenges have been observed following the consumption of wines and teas (Whitehead et al, 1995;Sera®ni et al, 1996Sera®ni et al, , 1998. Such results do not necessarily indicate that phenolics are transported to cellular sites within peripheral tissues where they could exert important antioxidant function.…”
Section: Discussionmentioning
confidence: 72%
“…Total phenols in plasma and urine were also estimated with Folin Ciocalteu reagent using a modi®cation of the method of Swain & Hillis (1959) which avoids interference from proteins in biological samples (Sera®ni et al, 1998). Plasma antioxidant capacity was estimated from its ferric reducing ability (FRAP) where development of an intense blue colour resulting from the conversion of a Fe(III)-2,4,6-Tri(2-pyridyl)-s-triazine (TPTZ) complex to Fe(II)-TPTZ is directly related to the amount of reductant present (Benzie & Strain, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported increases in antioxidant capacity of plasma following consumption of antioxidant-rich fruit, vegetables, teas, wines and grapejuice (Whitehead et al, 1995;Benzie et al, 1999;Kivits et al, 1997;Sera®ni et al, 1998;Duthie et al, 1998). This effect has been ascribed to the low molecular weight phenolics in many plant-based foods which can act as antioxidants because their extensive conjugated p-electron systems allow ready donation of electrons or hydrogens from the hydroxyl moieties to free radicals (Scott, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Total phenols in plasma and urine were also determined with Folin-Ciocalteu reagent, using a modi®cation to remove protein interference in the samples (Sera®ni et al, 1998). Vitamin C concentration in plasma and juice was measured by high pressure liquid chromatography (Ross, 1994).…”
Section: Methodsmentioning
confidence: 99%